A comparative study of intramedullary nailing versus minimally invasive percutaneous plate osteosynthesis for extra articular distal tibia fracture - Pasha, Rahil T.; Sasnur, Prakash A.; Basha K., Moinuddin; Zahid, Syed Hasan (International Journal of Research in Orthopaedics, 2024)
Background: Distal tibia fractures are among the most challenging orthopaedic injuries due to their subcutaneous location, limited blood supply and proximity to the ankle joint. These fractures often result in complications such as delayed-union, non-union, wound infection and malalignment. This study aims to compare the effectiveness of two minimally invasive surgical methods: Intramedullary Nailing (IMN) and Minimally Invasive Percutaneous Plate Osteosynthesis (MIPPO) in treating extra- articular distal tibia fractures. Methods: A prospective study was conducted on 30 patients with extra-articular distal tibia fractures. The participants were divided into two groups, 15 patients receiving IMN and 15 patients MIPPO. Clinical assessments were carried out to evaluate functional outcomes, union time and complications. Radiological evaluations were used to monitor the progress of fracture healing. Results: Both IMN and MIPPO were effective in treating distal tibia fractures, with each technique having its advantages and drawbacks. IMN showed a shorter union time and fewer wound complications compared to MIPPO, which demonstrated better alignment and fewer malunions. However, IMN was associated with a higher incidence of anterior knee pain, whereas MIPPO had more cases of implant irritation leading to reoperation. Conclusions: Both IMN and MIPPO offer viable treatment options for extra-articular distal tibia fractures. IMN is preferred in cases where early weight-bearing and faster union are critical, particularly in patients with soft tissue concerns. Conversely, MIPPO is advantageous in achieving better alignment and should be considered when soft tissue conditions allow. We conclude by Intramedullary Nailing as better treatment modality for distal tibia extra articular fractures.